Political Opportunities and China’s Proposing Behavior in the G20 - Hongsong Liu (Chinese Journal of International Review, 2019)
In global economic governance, political consensus reached by the G20 members plays an important role of defining governance ideas and governance directions as well as steering and boosting collective actions. Political opportunities are essential for the G20 members’ successful efforts to place their preferences into the political consensus of G20. This paper analyzes how the G20 members place their preferences into the political consensus of G20 through the lens of political opportunity, and provides a relatively detailed demonstration on China’s practice of proposing policy initiatives and placing its preferences into the political consensus of G20 by examining the cases of International Monetary Fund (IMF) quota reform and international financial regulation reform.